Volume 10B: Structures and Dynamics 2020
DOI: 10.1115/gt2020-14477
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spectral Method for Vibration-Induced High-Cycle Fatigue Evaluation of an HP Turbine Blade

Abstract: A method of fluid-structure interaction coupling is implemented for a forced-response, vibration-induced fatigue life estimation of a high-pressure turbine blade. Two simulations approaches; a two-way (fully-coupled) and one-way (uncoupled) methods are implemented to investigate the influence of fluidsolid coupling on a turbine blade structural response. The fatigue analysis is performed using the frequency domain spectral moments estimated from the response power spectral density of the two simulation cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Therefore, this shows the breakdown of such assumptions in the current case of a transonic flow field. A similar observation was made in Ubulom, 55 where it was reported that such assumptions can only hold at the onset of flutter and would likely break down for lightly damped profiles, and also under a transonic flow condition where even a seemingly small oscillation can lead to nonlinear behavior. Furthermore in Moffat and He, 54 this additional damping force was predicted to lag the blade motion in a typical forced-response vibration case.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, this shows the breakdown of such assumptions in the current case of a transonic flow field. A similar observation was made in Ubulom, 55 where it was reported that such assumptions can only hold at the onset of flutter and would likely break down for lightly damped profiles, and also under a transonic flow condition where even a seemingly small oscillation can lead to nonlinear behavior. Furthermore in Moffat and He, 54 this additional damping force was predicted to lag the blade motion in a typical forced-response vibration case.…”
Section: Discussionsupporting
confidence: 71%
“…In a classical mode I of crack growth process, it is well established that the slip processes and decohesion in front of the crack are mainly shear plane driven. 55 Similarly, in a stage II of crack growth process, although the dislocation mobility is controlled by the tensile strain present, the slip and decohesion process is also shear dependent. From a separate analysis of the above predicted stress histories, the shear stress histories were similar to that of the equivalent von Mises case of Figure 13, with the fully coupled case fluctuating about the mean position of the decoupled case.…”
Section: Discussionmentioning
confidence: 99%